Improving Oil Price forecasting using Regression-Relief-bases Indicators Selection Model - S. Al-Shamery, Eman; Al–Gashamy, Hussein (International Journal of Engineering and Technology, 2018)
Crude oil holds a vital and growing role in the local and global economy. The main goal of this study is to explore the effect of technical indicators in enhancing the capability of Sequential Minimal Optimization (SMO) to forecast the precise oil price. In addition, Relief algorithm reduces the dimensional space and eliminates irrelevant factors. 10-fold Cross validation testing method is used to train two main series of crude oil price, Brentand West Texas Intermediate (WTI). Further, Mean Absolute Error Â and Root Mean Squared Error are considered as evaluation criteria. A comparison has been implemented on input features with and without TIs. The results show that using Technical Indicators satisfy better results of prediction. The Accuracy rate is raised with MAE ratio 14:1 for Brent and 15:1 for WTI, while RMSE improved with ratio17:1 for Brent and 20:1 for WTI. Finally, The experimental result proved that the optimized model was superior when compared with Linear regression, MLP regression, and Gaussian in terms of prediction errors.Â Â